Impact of sympathetic nervous system on immune evasion in high-grade serous ovarian cancer: a review - Yu, Ruiyuan; Li, Yumeng; Jiang, Runze; Dang, Chunxiao; Zhai, Fengting (Frontiers in Oncology, 2025)
As the most frequent and aggressive subtype of ovarian cancer, high-grade serous ovarian cancer (HGSOC) often advances unnoticed due to its subtle early symptoms, which in turn leads to a significantly low five-year survival rate. The process of immune evasion, often achieved by constructing an immunosuppressive microenvironment through various pathways, stands as a critical feature of tumor biology. At the same time, emerging studies reveal a strong association between the sympathetic nervous system (SNS) and immune regulation in the tumor microenvironment (TME). In HGSOC, SNS activation releases neurotransmitters like norepinephrine, which affect immune cells, suppress their functions, weaken anti-tumor responses, and promote the recruitment and activation of immunosuppressive cells. By recruiting immune-suppressive cells, altering the extracellular matrix to construct physical barriers, and increasing pro-angiogenic signals, the SNS reshapes the tumor microenvironment in a way that hampers immunotherapy. Clinically, higher levels of SNS activation are linked to worse outcomes and therapeutic resistance in HGSOC. Additionally, preclinical studies demonstrate that targeting the SNS using β-adrenergic receptor inhibitors can improve immune activation and enhance treatment responses. Moving forward, research needs to further examine SNS mechanisms to support the development of advanced therapeutic strategies.